The bearded dragon - Miller, Jake, 1969- (New York : PowerKids Press, 2003)
Brief text describes the appearance, habitat, mating, family life, behavior, and predators of the bearded dragon, a friendly lizard found all over Australia.
Includes index.
Library Media Connection.
5.6
3-6
Keywords: Bearded dragons (Reptiles) -- Juvenile literature; Bearded dragons (Reptiles); Lizards; Bearded dragons (Reptiles); Lizards; Lizards; Zoology -- Australia